Acute kidney injury and chronic kidney disease in umbilical cord blood transplant recipients - Lopedote, Paolo; Xue, Elisabetta; Chotivatanapong, Julie; Pao, Emily C.; Wychera, Chiara; Dahlberg, Ann E.; Thur, Laurel; Roberts, Laura; Baker, Kelsey; Gooley, Ted A.; Hingorani, Sangeeta; Milano, Filippo (Frontiers in Oncology, 2023)
Introduction Acute kidney injury (AKI) is a frequent early complication post hematopoietic stem cell transplant (HSCT), associated with high morbidity and mortality. Cord blood transplant (CBT) recipients are potentially exposed to more nephrotoxic insults, compared to patients undergoing HSCT from other donor sources. We aimed to identify risk factors for AKI in patients undergoing CBT. We also aimed to identify the impact of AKI on chronic kidney disease (CKD) and survival outcomes by one-year post-CBT. Methods Adults and children who underwent a first CBT at our Institution were retrospectively evaluated. AKI was staged according to Kidney Disease Improving Global Outcomes (KDIGO) definitions. Cox regression models were used to estimate the association of demographic factors and post-CBT parameters with the cause-specific hazard of AKI. Results We identified 276 patients. Median age was 32 years, 28% (77/276) were children (<18 years) and 129 (47%) were white. A myeloablative conditioning regimen was administered to 243 patients (88%) and 248 (90%) received cyclosporine for GVHD prophylaxis. One-hundred and eighty-six patients (67%) developed AKI by day 60 post-transplant, with 72 (26%) developing severe AKI (stage 2 and 3). In a multivariable analysis, each increase in bilirubin level of 1 mg/dL was associated with a 23% increase in the risk of severe AKI (adjusted HR 1.23, 95% CI 1.13 – 1.34, p<.0001). Conversely, systemic steroid administration appeared to be protective of severe AKI (unadjusted HR 0.36, 95% CI 0.18 – 0.72, p=.004) in a univariate model . Two-hundred-forty-seven patients were evaluable at the one-year time point. Among those, 100 patients (40%) developed CKD one-year post-CBT. Severe AKI was associated with a higher hazard of non-relapse mortality (adjusted HR=3.26, 95% CI 1.65-6.45, p=.001) and overall mortality (adjusted HR=2.28, 95% CI 1.22-4.27, p=.01). Discussion AKI is a frequent complication after CBT and is associated with worse outcomes. Questions remain as to the mechanism of the protective role of steroids on kidney function in the setting of CBT.